Ageing Masculinities, Alzheimer's and Dementia Narratives - Sweney, Matthew; Kunow, Rüdiger; Hartung, Heike (Bloomsbury Studies in the Humanities, Ageing and Later Life, 2022)
This volume focuses on cultural representations of dementia as a disease of ageing masculinities and on male identity construction.